The design and synthesis of mycobacterium tuberculosis caseinolytic protease inhibitors - Shuro, Pious (My University, 2019)
Tuberculosis (TB) is the main cause of death from a single infectious agent, ranking above HIV/AIDS. Approximately 2.0 billion people worldwide are infected with Mycobacterium tuberculosis (M.tb) but only a fraction of 5-15% develop the TB disease and 1.5 million deaths were also estimated (worldwide). The emergence of Multi-drug resistant (MDR), Extensive –drug resistant (XDR) and Total- drug resistant (TDR) TB infections has increased the need or demand for researchers to discover and develop novel anti-TB drugs with a new and effective mode of action against drug resistant TB strains, with safe and short treatment time. This project was aimed at designing and synthesizing novel ecumicin derivatives as caseinolytic protease inhibitors with anti-tb activity This work describes the synthesis of ecumicin natural amino acids derivatives, cationic with lassomcyin residues derivatives, lysine cationic derivatives and N-methylated and peptoid derivatives. Previous studies propose that ecumicin binds to the acidic region of the (ATPase) or the ClpP proteolytic system or the allosteric site of ClpC. The designed peptides were synthesized using solid phase peptide synthesis and using various coupling conditions. Coupling conditions and amino acid sequences impacted the success of the synthesis of the derivatives with highly cationic peptides showing better results compared to N- methylated peptides and OxymaPure yielding better results compared to HATU coupling reagents. Successfully synthesized and purified peptides were tested for activity against Mycobacterium tuberculosis strain. For the tested compounds, non-showed any activity against Mycobacterium tuberculosis strain
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg In fulfillment of the requirements for the Degree of Master of Science May, 2019